ANALISIS PERSEPSI DAN PENGAMBILAN KEPUTUSAN KEUANGAN UMKM: Pelaku Usaha Kuliner di Jombang - DEWI PUSPITANINGSIH (JOURNAL KOPERASI DAN MANAJEMEN, 2025)
Purpose – This study aims to analyze the perceptions of culinary MSME (Micro, Small, and Medium Enterprises) owners in Jombang regarding financial management and to identify the processes behind their financial decision-making. The research focuses on how internal and external factors influence these decisions, as well as the meanings embedded in each financial choice made Design/methodology/approach – This research employed a qualitative approach with a case study design. Informants were selected using purposive sampling, with criteria including culinary business owners who had been operating for at least two years and were directly involved in managing their business finances. Data were collected through in-depth interviews, participant observation, and documentation review, then analyzed using thematic analysis. Data validity was ensured through source triangulation and methodological triangulation. Findings – The findings reveal that most culinary MSME owners in Jombang perceive financial management in a simple manner, with inconsistent separation between personal and business finances. Financial decisions are largely influenced by intuition, personal experience, and input from family or peers, while quantitative, data-driven considerations are rarely applied. Financial management strategies tend to be reactive, adjusting expenditures based on daily or weekly income, and are constrained by low financial literacy and limited access to formal financing. Research limitations/implications – This study was limited to culinary MSME owners located in Jombang, Indonesia, with at least two years of business operation. The findings may not be generalizable to other regions or sectors due to cultural, economic, and market differences. Furthermore, the qualitative nature of this research emphasizes depth over breadth, so the results are context-specific and may vary if applied in different settings. Originality/value – This study provides an original contribution by exploring the dimensions of perception and meaning behind financial decision-making among culinary MSMEs in Jombang. The qualitative approach enables the identification of non-financial factors, including emotional and socio-cultural aspects, which are often overlooked in quantitative studies. These findings can serve as a foundation for designing more contextual financial assistance programs tailored to the unique characteristics of local business owners Keyword : Culinary MSMEs; Financial Management; Decision-Making; Perception; Qualitative Research; Jombang